-6-3y=2

Simple and best practice solution for -6-3y=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6-3y=2 equation:


-6-3y=2

We simplify the equation to the form, which is simple to understand
-6-3y=2

We move all terms containing y to the left and all other terms to the right.
-3y=+2+6

We simplify left and right side of the equation.
-3y=+8

We divide both sides of the equation by -3 to get y.
y=-2.6666666666667

See similar equations:

| 125m+75m+48000=50000-200m | | -n=-8+2n | | 7d+2=9d-5 | | 4-5=22 | | 9+6+4x+9=x | | 30+2x=40+1x | | 2x+9-9x=13-15x+8x-4 | | 1x-7=-1 | | 3(2d+7)=29 | | 7z/8+z/4=-36/16 | | 29-5x=-8(x-1) | | 3+2a=7+3a | | 10x-46=7x+14 | | 7z/8+z/4=36/16 | | 6h-12=n+3 | | 6x-3+2x=9+6x | | 11x-12=4x+1 | | 8x+7-7x=32 | | 30+8x=-8-6(7-4x) | | 6p+4+8=-18 | | 0=13x-1.86x^2 | | -4(-c-g)=4c-8 | | x+5+2x=2x | | X^2-52x+640=0 | | 60-4x=5 | | 6(2x+2)=6x+48 | | 2n^3-2880n^2-24482n=0 | | W+0.02w=8.67 | | -5(4x-3)=-30-5x | | 13x*7(-3x-1)=-63 | | 0=x^2+1x-12 | | b-2.1=-4.9 |

Equations solver categories